The Impact of Gold Mining on Children's Education in Lele Village, District of Buru - TALAKUA, Jeane F. D.; WAISAPY, Jeanly (PT Batara Swastika Harati, 2023)
Gold mining also affects the education sector of local children, one of which is Lele Village, located in Lolong Guba Sub-district, Buru Regency. This problem is presented through qualitative research with descriptive methods that aim to describe the conditions and situations related to the impact of waste gold mining in Lele Village. The analytical methods used are participatory problem analysis and stakeholder analysis. The waste of gold mining in Lele Village is significant enough to affect the community's income. However, the impact on education can be that children experience a setback because children who participate in work tend to ignore school. When faced with economic problems, they have no choice, especially since working in this waste gold mine is quick to make money. Therefore, it requires the attention of the local government as well as indigenous peoples to care about resolving the phenomenon of children working in mining areas, as well as school-age people who do not continue their education.